Hydroxychloroquine and Covid-19, CFM opinion: Principiology, Contradictions and Complexity (Research, Society and Development, 2021)
The study proposes a principle review of the opinion related to the release of hydroxychloroquine by the Conselho Federal de Medicina (CFM). In the Opinion, CFM releases the doctor who prescribes ethical sanctions, based on the lack of other available medical resources, availability of the drug, low cost and the principle of autonomy. Disregarding the principiological relations, as well as the Biodireito, consumer protection code and other thoughts related to the civil and penal codes, it may expose the doctor to judicial imputations.